Biodiversity scientists must fight the creeping rise of extinction denial - Lees, Alexander C.; Attwood, Simon; Barlow, Jos; Phalan, Ben (Springer, 2020)
Efforts by conservation scientists to draw public attention to the biodiversity crisis are increasingly met with denialist rhetoric. A summary of some of the methods used by denialists to undermine scientific evidence on biodiversity loss, and outline pathways forward for the scientific community to counter misinformation are outlined.